The Knowledge of the Youth Centers’ Members with the Concept of Reproductive Health: A Field Study (2021-2024) - AlHrout, Mo’ath Mahmoud (Jordan Journal of Social Sciences, 2024)
This study aimed to identify the knowledge level of youth centers' members with the concept of reproductive health following the institutional strategic plan of the ministry of youth (2021-2024). The study drew on the descriptive analytical method. A specifically-built questionnaire was used to collect the data. A sample of (279) members of the administrative boards in the typical youth centers in the central governorates (Amman, Zarqa, Balqa, and Madaba) was chosen. The study showed that the age range of the administrative boards of the typical youth centers for males and females was between 14-17 years old. The longest period of time for the affiliation with youth centers was between 3-5 years. The results of the study indicated that there were statistically significant differences due to the location of the center variable according to the governorates regarding the knowledge level of the concept of reproductive health, its component, the concept of family planning, the methods used in family planning, knowledge of the Islamic opinion of family planning, and related diseases. Additionally, the study found that were statistically significant differences due to the sex variable in maintaining good reproductive health and knowledge of reproductive health. This is effectively attributed to the fact that males think that reproductive health only relates to females. Moreover, the results indicated that the percentage of members who did not participate in workshops or lectures relating to reproductive health in youth centers was (59%). The study recommended taking the necessary steps to refer to the Arab Jordanian culture and Islamic teachings in the workshops of reproductive health. Additionally, different partners should provide awareness programs on reproductive health concepts for adolescents and young people in youth centers. They should consider equitable geographical distribution in implementing and following up related programs and trainings so as to ensure that the desired goals are achieved in a proper manner.